Preferential Trade Agreements And Their Role In World Trade - Medvedev, Denis (The World Bank, 2006)
The author investigates the effects of preferential trade agreements (PTAs) on bilateral trade flows using a comprehensive database of PTAs in force and a detailed matrix of world trade. He shows that total trade between PTA partners is a poor proxy for preferential trade (trade in tariff lines where preferences are likely to matter): while the former amounted to one-third of global trade in 2000-02, the latter was between one-sixth and one-tenth of world trade. His gravity model estimates indicate that using total rather than preferential trade to assess the impact of PTAs leads to a significant downward bias in the PTA coefficient. The author finds that product exclusions and long phase-in periods significantly limit preferential trade, and their removal could more than double trade in tariff lines above 3 percent of most-favored-nation (MFN) duties. He also shows that the effects of PTAs on trade vary by type of agreement and are increasing in the incomes of PTA partners